2021
DOI: 10.1097/j.pain.0000000000002353
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cδ as a neuronal mechanism for headache in a chronic intermittent nitroglycerin model of migraine in mice

Abstract: Migraine is one of the most common neurological disorders characterized by recurrent attacks of typically throbbing and unilateral headaches, affecting up to 20% of the population worldwide. Despite the high prevalence and severity of this primary headache disorder, it remains to be a challenge to fully understand and treat migraine headaches. By characterizing and validating a mouse migraine model, this study aimed to investigate the functional contribution of protein kinase C (PKC) isoforms in migraine. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In agreement with all pivotal clinical studies on the efficacy of the CGRP monoclonal antibodies as well as the gepants (1)(2)(3)(4)(5)(6)(7), behavioral studies in rodents have found therapeutic effects of CGRP inhibitors in several models of headache, including systemic glyceryl trinitrate (GTN) (8)(9)(10)(11), dural application of inflammatory mediators (12) or potassium chloride (13,14), spontaneous facial hypersensitivity (10,15), traumatic brain injury (16,17), medication overuse headache (18), CGRP-induced photophobia (19), and umbelluloneinduced hyperalgesic priming (20), and electrophysiological or fos expression studies found inhibitory effects of these agents in response to GTN or other nitric oxide donors (21)(22)(23), or direct electrical or chemical stimulation of the dura (24,25), but not cortical spreading depression (CSD) (24) -where the observed reduction in percentage of activated Ad did not reach statistical significance during the relatively short (1 hr) post-CSD recording period.…”
Section: Introductionsupporting
confidence: 57%
“…In agreement with all pivotal clinical studies on the efficacy of the CGRP monoclonal antibodies as well as the gepants (1)(2)(3)(4)(5)(6)(7), behavioral studies in rodents have found therapeutic effects of CGRP inhibitors in several models of headache, including systemic glyceryl trinitrate (GTN) (8)(9)(10)(11), dural application of inflammatory mediators (12) or potassium chloride (13,14), spontaneous facial hypersensitivity (10,15), traumatic brain injury (16,17), medication overuse headache (18), CGRP-induced photophobia (19), and umbelluloneinduced hyperalgesic priming (20), and electrophysiological or fos expression studies found inhibitory effects of these agents in response to GTN or other nitric oxide donors (21)(22)(23), or direct electrical or chemical stimulation of the dura (24,25), but not cortical spreading depression (CSD) (24) -where the observed reduction in percentage of activated Ad did not reach statistical significance during the relatively short (1 hr) post-CSD recording period.…”
Section: Introductionsupporting
confidence: 57%
“…anti-CGRP-mAbs (monoclonal antibodies), anti-CGRP/R-mAbs, CGRP receptor antagonists] in migraine prevention 8-12 and resolution. 13 , 14 In agreement with these clinical studies, behavioural studies in rodents have found therapeutic effects of CGRP inhibitors in several models of headache, including systemic glyceryl trinitrate (GTN), 15-18 dural application of inflammatory mediators 19 or potassium chloride, 20 , 21 medication overuse headache, 22 CGRP-induced photophobia 23 and umbellulone-induced hyperalgesic priming. 24 Similarly, physiological studies found inhibitory effects of these agents in response to systemic administration of GTN or other nitric oxide donors, 25-27 direct electrical or chemical stimulation of the dura 28 , 29 and cortical spreading depression (CSD).…”
Section: Introductionmentioning
confidence: 62%
“…7 ), suggesting a potential causal relationship between these neurons and migraine chronification. Although prior studies have indicated that sensitization of TG neurons are responsible for the pain in this model [ 49 51 ], our study provides an alternative perspective that there is a cell-type specific central mechanism that regulates the trigeminal or extra-trigeminal nociceptive input in CM. Notably, specifically silencing these CeA PKC-δ positive neurons with chemogenetics, without directly intervening the TG, could still reduce the CGRP expression in the TG, which further suggests a possible top-down mechanism of these neurons in regulating pain.…”
Section: Discussionmentioning
confidence: 83%